Comment on Machine Learning–Based Prediction of Histopathological Classification in Colorectal Polyps - Akca, Serdar; Cagin Buldukoglu, Osman; Egemen Atar, Galip; Hilmi Cekin, Ayhan (Turkish Journal of Gastroenterology, 2026)
Cite this article as: Akca S, Buldukoglu OC, Atar GE, Cekin AH. Comment on machine learning–based prediction of histopathological classification in colorectal polyps. Turk J Gastroenterol. Published online February 20, 2026. doi: 10.5152/tjg.2026.25816.